2007
DOI: 10.1523/jneurosci.4371-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline Reduces Microglial Activation and Improves Behavioral Deficits in a Transgenic Model of Cerebral Microvascular Amyloid

Abstract: Cerebral microvascular amyloid ␤ protein (A␤) deposition and associated neuroinflammation is increasingly recognized as an important component leading to cognitive impairment in Alzheimer's disease and related cerebral amyloid angiopathy disorders. Transgenic mice expressing the vasculotropic Dutch/Iowa (E693Q/D694N) mutant human A␤ precursor protein in brain (Tg-SwDI) accumulate abundant cerebral microvascular fibrillar amyloid deposits and exhibit robust neuroinflammation. In the present study, we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
136
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(148 citation statements)
references
References 44 publications
6
136
0
Order By: Relevance
“…F/T, Frontotemporal cortex. fibrillar amyloid, but not diffuse A␤ plaque deposits, in Tg-SwDI/ muAPOE mice (Miao et al, 2005a,b;Fan et al, 2007). Because the current results clearly show that Tg-SwDI mice on human APOE backgrounds shift the distribution of fibrillar amyloid from the microvascular deposits to parenchymal plaques, we investigated whether this altered the spatial accumulation of neuroinflammatory reactive astrocytes and activated microglia.…”
Section: Increased Numbers Of Neuroinflammatory Cells Correlate With mentioning
confidence: 68%
See 2 more Smart Citations
“…F/T, Frontotemporal cortex. fibrillar amyloid, but not diffuse A␤ plaque deposits, in Tg-SwDI/ muAPOE mice (Miao et al, 2005a,b;Fan et al, 2007). Because the current results clearly show that Tg-SwDI mice on human APOE backgrounds shift the distribution of fibrillar amyloid from the microvascular deposits to parenchymal plaques, we investigated whether this altered the spatial accumulation of neuroinflammatory reactive astrocytes and activated microglia.…”
Section: Increased Numbers Of Neuroinflammatory Cells Correlate With mentioning
confidence: 68%
“…In Tg-SwDI/muAPOE mice, activated microglia are tightly associated with the development of cerebral microvascular fibrillar amyloid (Miao et al, 2005a;Fan et al, 2007;Xu et al, 2007). In these mice, the abundant parenchymal diffuse A␤ deposits do not appear to promote microglial activation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…One potential drug already being investigated is (+)-naloxone, which inhibits TLR4-mediated microglial activation and decreases proinflammatory cytokine expression [63]. Another microglia-related drug is minocycline, which reduces microglial and neuroimmune activation [64]. Minocycline also decreases ethanol consumption, albeit by an unknown mechanism [65].…”
Section: Tlr-specific Drugs Alter Alcohol Consumptionmentioning
confidence: 99%
“…For addiction, in particular, studies have highlighted the glutamatergic and DA effects of minocycline, which in turn have been implicated in addiction etiology (Kalivas & Volkow, 2005). In addition, the effects of minocycline on neuroimmune and cytokine expression have been emphasized as potential therapeutic targets for this medication (Fan et al, 2007;Mishra & Basu, 2008). Preclinical studies have found that minocycline attenuated NMDA receptor antagonist-induced cognitive impairment in rodents (Fujita et al, 2008;Munzar, Li, Nicholson, Wiley, & Balster, 2002).…”
Section: Minocycline and Doxycyclinementioning
confidence: 99%